The Effects of Methane Storage Capacity Using Telmisartan Organotin (IV) Complex - Emad Yousif (Journal of Global Pharma Technology, 2016)
The fabrication of porous dibutylorganotin (IV) complex as methane storage was successful. Interesting physiochemical properties for diorganotin (IV) complex were observed using a combination of several techniques such as scanning electron microscopy, Brunauer–Emmett–Teller and nitrogen adsorption–desorption isotherm, Barrett–Joyner–Halenda and H-sorb 2600 analyzer. The mesoporous complex exhibit tunable porosity with Brunauer–Emmett–Teller surface area (SABET = 130.357 m2.g-1), pore volume (0.162 cm3.g–1) and narrow pore size distribution; the complex was found to has high physico-chemical stability. At 323 K and 50 bars, the complex has methane uptake (up to 1.116 cm3·g–1). The field emission scanning electron microscopy images, at different 100 and 50 µm magnification powers were confirmed, the morphological images of the polymeric film showed a rough surface.  Keywords: Gas storage; Methane capture; Diorganotin (IV) complex; Field emission scanning electronic microscope.